Identity transformations in the context of information-technological revolution (socio-cultural aspect) - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The problem of identity is perpetually urgent, however, recently the number of publications devoted to the analysis of specific varieties of identities, their characteristics, factors influencing the formation of identities in the new socio-cultural conditions, has significantly increased. Such interest is generated by the processes of globalization, virtualization, creation of online communities, which significantly influence the conditions of identity formation. It makes researchers to adjust the existing concepts of identity, focusing on its transformations in the new socio-cultural reality. Aim and tasks is the identification of identity transformation features in the conditions of information and technological revolution. Research methods. A sociocultural methodological approach is applied to consider identity transformations in the context of ongoing changes. By means of comparative analysis, peculiarities in the coverage of the concept and nature of identity in different theories are revealed. Research results. A philosophical study of the phenomenon of identity has a centuries-old history dating back to the Antiquity. In the classical philosophical tradition, identity is associated with the most important characteristic of the individual, which presupposes the preservation of identity and counteracts "differences". In the postmodern era, attention to the term "identity" was exacerbated by the loss of confidence in traditional conceptualism, which is responsible for rising of ambiguity of the definitions themselves. In today's context, this problem continues to be revealed by contemporary researchers who declare new views on identity and the features of its transformation in a situation where the relationship between the individual and the social becomes a contradiction. Discussion. With the rapid growth of socio-cultural development, traditional social institutions have been gradually losing their stability, causing person’s need to choose new identities. According to modern researchers, in the virtual culture itself changes the principle of existence and understanding of culture due to the "disappearance of meaning" sign. Conclusion. It is obvious from the research, a necessary condition for successful social adaptation of modern man to new socio-cultural conditions, is his ability to find and preserve identity. After all, each of us from time to time is forced to solve a difficult task: how to protect ourselves in the new social situations, to maintain a personal integrity and stability.